Pelatihan Pengolahan Jajanan Sehat Anak Sekolah kepada UMKM Makanan Jajanan Di Kecamatan Ubud Kabupaten Gianyar - Ni Putu Agustini; A.A.N. Kusumajaya; I G.P. Sudita Puryana (Poltekkes Kemenkes Denpasar, 2019)
Children are a group at high risk of contracting the disease through food or drink.Based on the results of the research by Agustini and Kusumayanti (2016) on the Development of Traditional Balinese Snacks to Healthy Snacks for School Children in Gianyar Regency stated that the results of the development of these snacks had a good acceptability (93.15%) in school children.Therefore to increase the availability of healthy snacks for school children, the results of this study were followed up in the form of community service, with the aim of improving the skills of processing healthy snacks through training.Participants in the training included: school children, school canteen managers, snacks sellers and school teachers as many as 16 people.The results of community service were able to increase knowledge from an average of 63.75 to 86.35.The participants' skills in making healthy snacks for school children are quite good, because snacks that are processed are modified traditional snacks, which are commonly done by the local community.The follow-up of this training is the application of skills in processing healthy snacks both at school canteens, snack processors, and monitoring school children snacks by school teachers.Keywords: training, processing, healthy snacks, school children